Evaluation of processed and ultra-processed foods: An analysis before the implementation of front-of-package labeling in Peru - Mamani-Urrutia, Víctor Alfonso (2021)
Objective. The objective of the current study was to evaluate critical nutrients of industrialized foods and compare them with the technical parameters established in the Peruvian regulations, in its two stages of implementation, referring to front-of-package labeling before the beginning of its validity in June 2019. Methods. Cross-sectional study in which the critical nutrients of sodium, total sugar, saturated fat and transfat were analyzed from data declared in the nutritional labels of 511 processed and ultra-processed foods that were part of the products purchased for the consumption of 88 families of students from one private university in Lima. The technical parameters used to evaluate the critical nutrients are those established in the Regulation of Law 30021. All analyses were carried out with Excel and SPSS version 21, Student’s t-statistics and McNemar’s test were used. Results. 79 processed foods and 432 ultra-processed foods were analyzed. Of the total processed and ultra-processed products evaluated, it was found that for sodium 14.3% and 37.2% respectively exceeded the parameters in the first and second stages established in the regulations; for sugar 54.2% and 62.6%; while for saturated fats 52.8% and 59.5%, respectively. Solid foods are those that will have the greatest changes in front labeling between the first and second stages of implementation, unlike liquids that without changing the composition of their products, their front labeling would not vary significantly. Conclusions. The saturated fat present in solid products (processed and ultra-processed), exceeds the parameters in both stages of implementation in most products. Of the foods compared, regardless of type and category, the critical nutrient sugar was the one that was highly present in most of the products evaluated for the first and second stages of implementation.